Electroacupuncture Reduces Body Weight by Regulating Fat Browning-Related Proteins of Adipose Tissue in HFD-Induced Obese Mice - Lu, Sheng-Feng; Tang, Yue-Xia; Zhang, Tao; Fu, Shu-Ping; Hong, Hao; Cheng, Yu; Xu, Hou-Xi; Jing, Xing-Yue; Yu, Mei-Ling; Zhu, Bing-Mei (Frontiers in Psychiatry, 2019)
Objective: To study the influence of electroacupucntre (EA) and its possible mechanisms on adipose tissue of HFD-induced obese mice. Methods: Three-week-old male C56BL/6 mice were randomly divided into a chow diet group (CD) and a high fat diet (HFD) group. After 12 weeks, CD and HFD mice were randomly divided into two groups respectively to receive EA or not for 4 weeks. Body weight (BW) was monitored. Intraperitoneal glucose tolerance test and metabolic chamber recordings were performed. Blood samples and adipose tissue were collected for the analysis of leptin, triglyceride levels and fat browning-related proteins. Results: EA significantly reduced food intake, BW and WAT/BW ratio, decreased the adipocyte size and serum concentrations of triglyceride (TG) and cholesterol, and increased oxygen consumption in HFD mice. Compared with the CD mice, the HFD mice had elevated fasting serum glucose level, impaired glucose tolerance, however these parameters were decreased by EA treatment. Meanwhile, EA promoted the protein and mRNA expressions of UCP1, PRDM16, and PGC-1α in adipose tissue, and activated sympathetic nerves via p-TH, A2AR and β3AR in white adipose tissue. Conclusions: EA reduced food intake, BW, TG and cholesterol, improved glucose tolerance in the HFD mice. This ameliorative effect of EA on obesity-related symptoms associated with its promoted adipose tissue plasticity via activating sympathetic nerves.